Investigation of attitudes toward mental illness among nursing students in Indonesia - Sri Padma Sari; Estin Yuliastuti (International Journal of Nursing Sciences, 2018)
Objective: People with mental illness (PMI) are often stigmatized or experience negative attitudes from society. In particular, nursing students’ attitudes toward PMI will influence the quality of care these patients receive. Some factors influencing attitudes toward PMI among nursing students have been identified. The present study aimed to examine factors influencing attitudes toward mental illness among nursing students in Indonesia. Methods: Nursing students (n = 317) were assessed for attitudes toward mental illness using the Community Attitude toward the Mentally Ill questionnaire. Details regarding sociodemographic variables (age, gender, ethnicity, year of study, monthly family income, personal experience with mental illness, family history of mental illness, and knowing or having direct contact with PMI) and knowledge about mental illness by using Mental Health Knowledge Schedule questionnaire were also obtained. Results: The mean Community Attitude toward the Mentally Ill questionnaire score was 103.75 ± 9.15, with the highest mean of the four subscales being that of authoritarianism 27.97 ± 2.87 followed by social restrictiveness, community mental health ideology, and benevolence 27.52 ± 3.68, 24.38 ± 3.80, and 23.89 ± 3.27, respectively. The factors significantly associated with nursing students’ attitudes toward mental illness were age (r = −0.18, P = 0.001), year of study (H = 16.65, P < 0.001), knowing or having direct contact with PMI (Z = −2.35, P = 0.019), and knowledge of mental illness (r = −0.22, P < 0.001). Conclusions: Several demographic variables, direct contact with PMI, and level of knowledge about mental illness can contribute to variations in attitudes toward PMI among nursing students in Indonesia. Education and direct contact with PMI serve as intervention strategies to reduce negative attitudes and stigma associated with mental illness among nursing students. Keywords: Attitude, Knowledge, Psychotic disorders, Students, Nursing